Evaluación y planteamiento de mejoras del proceso de manufactura de jeans de una empresa local dedicada a la confección de ropa sport mediante un modelo de simulación en witness - Arias Muñoz, Oscar Luis (2009)
This article contains the synthesis of the study performed for the evaluation and presentation of improvements of the process of the manufacture of men’s and women’s jeans with false or real pockets of a local company dedicated to the preparation of casual wear. The production line was analyzed using simulation as the main tool. A simulation model for the present situation was developed, validating it against the collected input data. Also modifications based on the proposals of improvement obtained from the initial experimentation were developed to two simulation models, whose objectives were to increase the production of the line, obtaining more finished product in comparison to the initial situation. Subsequent to the validation of both modified models, an analysis of the final experimentation was realized, in which it was demonstrated that the application of any of the two proposals of improvement would conclude in a significant increase in the daily production, and under a study of cost and benefit it was managed to demonstrate that both proposals of improvement turned out to have a significant yield, which with no doubt is highly beneficial for the company.